Maturity Level of Patient Safety Culture in Makassar City Hospital - Fridawaty Rivai; Irwandy; Siti Fatmala Rezeki; Syahrir Andi Pasinringi (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
The maturity of a patient safety culture is a step in developing a hospital patient safety culture. This research aims to determine the maturity level of patient safety culture in Makassar City hospitals. Furthermore, it is a quantitative study with a cross-sectional approach and was carried out at Public and Private Hospitals with the 2012 KARS Plenary level accreditation status in 2020. The purposive sampling method was used for the selection of the study locations and the selected hospital was the RSUD Haji Makassar, Hasanuddin University Hospital Makassar (belonging to the Ministry of Education and Culture), and Awal Bros Makassar Hospital (privately owned). The determination of the sample size was adjusted to the total number of employees of the hospital in which the research wasperformed, namely about 474 samples. The data collection tool contains a patient safety culture questionnaire based on the MaPSaF (Manchester Patient Safety Framework) instrument containing 5 levels of patient safety culture. The results showed that the maturity level of the patient safety culture in Makassar City hospital, the generative category was the largest choice, namely 391 respondents (82.5%) and the least in the reactive category was 1 respondent (0.2%). The three hospitals have maturity levels of patient safety in the generative category. It is hoped that the Makassar City hospital will be able to maintain the maturity of patient safety culture by paying attention to teamwork and responsibility by implementing a patient safety culture.